Formation rate as parameter to distinguish nucleation from hydrate massive growth phase: Experimental investigation in presence of two different porous media - Alberto Maria Gambelli; Federico Rossi (Experimental Thermal and Fluid Science, 2021)
Methane hydrate formation was tested in presence of two different porous media. Despite silica, the second sand contains several other compounds and grains are different from each other. The evaluation of the hydrate formation rate along the whole experiment, allowed to well distinguish the nucleation from the hydrate growth phase, without further analyses: all diagrams presented an almost equal trend. As soon the reaction begun, elevated formation rate values were measured. In almost all tests, after a few tens of minutes, values dropped and then assumed a horizontal trend, thus defining a “elbow point”, which was considered the key element to separate the two different phases. Analyses about moles of hydrate formed, together with pressure and temperature trends over time, revealed that this natural sand was a weak thermodynamic inhibitor. Conversely, the hydrate formation rate proved that it acted as strong kinetic inhibitor, in particular during the hydrate growth phase.